Propofol EC50 for inducing loss of consciousness in patients under combined epidural-general anesthesia or general anesthesia alone: a randomized double-blind study - Wang, Jiangling; Shen, Yajian; Guo, Wenjing; Zhang, Wen; Cui, Xiaoying; Cai, Shunv; Chen, Xinzhong (Frontiers in Medicine, 2023)
Background: Combined epidural-general anesthesia (GA+EA) has been recommended as a preferred technique for both thoracic or abdominal surgery. The epidural anesthesia on the general anesthetic (GA) requirements has not been well investigated. Therefore, we conducted the present study to explore the predicted effectsite concentration of propofol (Ceprop) required for achieving loss of consciousness (LOC) in 50% patients (EC50) with or without epidural anesthesia.Methods: Sixty patients scheduled for gastrectomy were randomized into GA+EA group or GA Alone group to receive general anesthesia alone. Ropivacaine 0.375% was used for epidural anesthesia to achieve a sensory level of T4 or above prior to induction of general anesthesia. The EC50 of predicted Ceprop for LOC was determined by updown sequential method. The consumptions of anesthetics, emergence time from anesthesia and postoperative outcomes were also recorded and compared.The EC50 of predicted Ceprop for LOC was lower in GA+EA group than that in GA Alone group [2.97 (95% CI: 2.63 -3.31) vs 3.36 (95% CI: 3.19 -3.53) μg•ml -1 , (P = 0.036)]. The consumptions of anesthetics were lower in GA+EA group than that in GA Alone group (propofol: 0.11 ± 0.02 vs 0.13 ± 0.02 mg•kg-1•min-1, P = 0.014; remifentanil: 0.08 ± 0.03 vs 0.14 ± 0.04 μg•kg-1•min-1, P < 0.001). The emergence time were shorter in GA+EA group than in GA alone group (16.0 vs 20.5 min, P = 0.013).The concomitant epidural anesthesia reduced by 15% the EC50 of predicted Ceprop for LOC, decreased the consumptions of propofol and remifentanil during maintenance of anesthesia, fasten recovery from anesthesia.